2021
DOI: 10.1017/s1355617720001319
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Memory Fluency Reductions in Cognitively Unimpaired Middle-Aged and Older Adults at Increased Risk for Alzheimer’s Disease Dementia

Abstract: Objective: Recent research has revealed that cognitively unimpaired older adults who are at higher risk for developing Alzheimer’s disease (AD) dementia often exhibit subtle cognitive alterations in their neuropsychological profiles. Emerging evidence suggests that autobiographical memory, which is memory for personal events and knowledge, may be sensitive to early AD-related cognitive alterations. In the present study, we investigated whether the rapid generation of autobiographical memory category exemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…These findings support the specificity of the EAM condition to test episodic components of autobiographical memory, as well as the suitability of the enPS condition as a measure of context-dependent, experience-near personal semantics. The notion that the AFT effectively taps enPS also is in line with the results of a recent study, in which performance in both the EAM and enPS condition of the AFT was found to be reduced in cognitively unimpaired older adults at risk to develop Alzheimer’s disease (Grilli et al, 2021 ). Importantly, the AFT requires participants to access autobiographical memories from different life periods (see below); thus, this feature further allows to ensure that the retrieved EAMs and enPS are temporally contextualized and to consistently sample across individuals’ memories, providing a way to finely assess individual differences in the access to autobiographical memories.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings support the specificity of the EAM condition to test episodic components of autobiographical memory, as well as the suitability of the enPS condition as a measure of context-dependent, experience-near personal semantics. The notion that the AFT effectively taps enPS also is in line with the results of a recent study, in which performance in both the EAM and enPS condition of the AFT was found to be reduced in cognitively unimpaired older adults at risk to develop Alzheimer’s disease (Grilli et al, 2021 ). Importantly, the AFT requires participants to access autobiographical memories from different life periods (see below); thus, this feature further allows to ensure that the retrieved EAMs and enPS are temporally contextualized and to consistently sample across individuals’ memories, providing a way to finely assess individual differences in the access to autobiographical memories.…”
Section: Introductionsupporting
confidence: 83%
“…The present study has different limitations. As mentioned, because the AFT does not require to elaborate on retrieved items, this test mainly assesses individual variations in the strategic retrieval of autobiographical memories (Grilli et al, 2021 ). Thus, present results are not directly informative of connectivity patterns associated with complete access and elaboration of such memories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, prior studies have shown that Alzheimer’s disease risk-related neural alterations in the hippocampus and its cortical connections are linked to cognitive mechanisms that may be needed to retrieve episodic details of past events, including spatial context memory, verbal memory recall, and cognitive control (Rajah et al, 2017; Shafer et al, 2021; Westlye et al, 2012). Older adult APOE4 carriers have deficits in other hippocampally dependent memory mechanisms that may also have a role in episodic detail generation, such as autobiographical category fluency and memory consolidation (Grilli et al, 2021; Tort-Merino et al, 2020; Zimmermann & Butler, 2018). Therefore, while the present study raises doubt about the role of relational processing, other cognitive mechanisms dependent on the hippocampus and its cortical connections may account for APOE4-associated reductions in episodic detail generation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, direct and generative retrieval may form a continuum of ease of retrieval. Earlier researchers (e.g., Benjamin & Bjork, 2014; Dritschel et al, 1992; Grilli et al, 2021) used the concepts of memory/retrieval fluency to denote the subjective experience of the ease of retrieval. The self-report measure of retrieval used here corresponds to the same concept.…”
Section: Discussionmentioning
confidence: 99%